Toward Mental Health-Oriented School Management: Systematic Review and Development of the MH-OELF - Muhammad Arsyad; Aslamiah Aslamiah (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study systematically reviews literature on educational leadership in school mental health contexts and develops the Mental Health-Oriented Educational Leadership Framework (MH-OELF) for Indonesian secondary schools. Guided by PRISMA 2020, the review searched Scopus, Web of Science, SSCI/ESCI, PubMed, DOAJ, and SINTA for English articles published from 2020–2025. From 212 records, 23 studies met the inclusion criteria and were analyzed through thematic coding. The synthesis yielded five interrelated dimensions: wellbeing-oriented vision, collaborative and distributed structures, tiered and systemic management, data-informed reflective practice, and cultural-contextual alignment. Findings show that effective mental health leadership depends on integrating these dimensions into a coherent whole-school ecosystem rather than applying isolated interventions. The proposed MH-OELF positions principals as adaptive system leaders who align policy, culture, and practice to sustain mentally healthy schools. The framework offers theoretical and practical guidance for school leaders, teachers, and policymakers in designing context-responsive mental health management in secondary education settings.